EFL Studentsâ€™ Perception on the Use of â€œRhetorical PrÃ©cisâ€ as a Summarizing Template - Panggalih, Wahyun Bardianing; Cahyono, Bambang Yudi (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2020)
For university students, a skill in writing a good summary of articles, books and other sources is very important. Rhetorical PrÃ©cis, a summarizing template that consists of four dense and direct sentences, can be used to compose a precise summary. This research aims at exploring EFL studentsâ€™ perceptions of the use of Rhetorical PrÃ©cis. Using a survey study, a five-degree questionnaire was spread out to 47 students who had attended the Critical Reading course at a reputable university in Surabaya, Indonesia. The data from the questionnaire were analyzed quantitatively. In addition, a semi-structured interview was held with four of the students. The interview was recorded and transcribed to meet the need of this study. The findings of this study showed that most of the students had positive perceptions of each element of Rhetorical PrÃ©cis. In short, the students perceived that the Rhetorical PrÃ©cis summarizing template could be usedÂ by the students to make a summary of the original texts precisely and accurately.